INFLUENCE OF THE DRUG FAGOMAST ON THE VITAL ACTIVITY OF CILIATES AND THE MUCOUS MEMBRANE OF THE EYES OF RABBITS - Horiuk, Y. V.; Kukhtyn, M. D.; V. V. , Horiuk; Mizyk, V. P. (Podilian Bulletin: Agriculture, Engineering, Economics, 2022)
Phage therapy is an alternative in the treatment of bacterial infections caused by antibiotic-resistant strains of bacteria, including mastitis in cows. Bacteriophage-based drugs for the treatment of mastitis in cows shall comply with the standards usually applied to pharmaceutical products. The aim of the work is to investigate the effect of the phage drug Fagomast on the vital activity of the ciliate Tetrachymena pyriformis and its possible irritating effect on the mucous membrane of the eyes of rabbits. For this purpose, a certified museum strain of the ciliate Tetrachymena pyriformis WH-14 has been used in accordance with generally accepted recommendations. To sterile test tubes with drug solutions has been added 0.05 ml of a 72-hour ciliate culture. After 0.5, 1 and 96 hours microscopy has been performed: the number of ciliates in the Goryaev chamber has been counted and their mobility has been determined. Each dilution of the drug has been studied in triplicate. Evaluation of the harmful (irritating) effect of phage drug solutions on the mucous membrane of the eyes of rabbits has been performed in accordance with all bioethical standards of animal handling. Each concentration of the drug has been instilled 2-3 drops into the conjunctival sac of one eye of the rabbit, and the other eye has been served as a control. The drug has been applied twice a day for 5 days. According to the results of research, it has been found that at the concentration of phages from 104 to 109 PFU/ml in the drug there is no change in motor activity and pathological abnormalities in the cells of ciliates. When determining the local irritating effect of Fagomast on the mucous membranes of the eyes of a rabbit, no visible changes have been observed both for the applying of the drug in the amount of phage parts of 104 PFU/ml and at the maximum content of 109 PFU/ml. Therefore, toxicological studies have shown that the bacteriophage-based drug Fagomast developed by us for the treatment of mastitis in cows can be recommended for further production tests.